1995
DOI: 10.1016/s0008-6363(95)00017-8
|View full text |Cite
|
Sign up to set email alerts
|

Vascular acetylcholine response during chronic NO synthase inhibition: in vivo versus in vitro

Abstract: Objective: The aim of this study was to compare the response to NO-mediated vasodilators in vivo and in vitro during chronic NO synthase inhibition. Methds: NG-Nitro-L-arginine-methyl ester (L-NAME, 0.4 g/l) or vehicle was administered in the drinking water for 6 weeks to male Wistar rats weighing 220-240 g. The effect of acetylcholine and sodium nitroprusside was examined in vivo, on systemic blood pressure and heart rate and in vitro, on the precontracted isolated mesenteric artery. The in vivo response to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…It can be secondary to a pharmacological effect of the drug on the endothelium. In this regard, it has been shown that in vivo inhibition of nitric oxide biosynthesis by chronic administration of L-arginine analogues leads to a reduced response of rat arterioles to norepinephrine, 26 a situation comparable with the one observed in the present study in which CsA caused a severe impairment in nitric oxide mediated vasorelaxation.…”
Section: Discussionsupporting
confidence: 90%
“…It can be secondary to a pharmacological effect of the drug on the endothelium. In this regard, it has been shown that in vivo inhibition of nitric oxide biosynthesis by chronic administration of L-arginine analogues leads to a reduced response of rat arterioles to norepinephrine, 26 a situation comparable with the one observed in the present study in which CsA caused a severe impairment in nitric oxide mediated vasorelaxation.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the enhanced extent of hypotension in SHR did not change after administration of molsidomine or PETN. The present findings are similar to those obtained in NO-deficient hypertension (6,8) although the etiopathogenic background, NO production, NO level, and cGMP level are different in these two experimental models of hypertension (29).…”
Section: Discussionsupporting
confidence: 91%
“…Even NO release, measured directly close to the endothelial layer in the femoral artery of the dog, decreased after NO synthase inhibition (4). In contrast, experiments performed on conscious animals, animals under anesthesia, and moreover, under various types of anesthesia, with NO synthase inhibition and consequent increased blood pressure, have demonstrated hypotension elicited by ACh (5)(6)(7). Previous studies by our group showed paradoxically amplified ACh hypotension not only after a short period of time (1-2 h) but also 6 weeks after NO synthase inhibition, which was accompanied by sustained high blood pressure (8).…”
Section: Introductionmentioning
confidence: 85%
“…ACh may have other effects on the endothelium, and may cause the release of endothelial-derived contracting factor (EDCF) or endothelial-derived hyperpolarizing factor (EDHF) [22]. In the absence of endothelium, ACh constricts the small resistance vessel [23].…”
Section: Discusssionmentioning
confidence: 99%